RELIABILITY ASSESSMENT OF EKPOMA 33/11KV INJECTION SUBSTATION DISTRIBUTION NETWORK - AIBANGBEE, J.O; IKHELOA, S.O. (FUDMA Journal of Sciences, 2025)
Power system reliability is the probability that an electric power system can perform required functions satisfactorily under given conditions for a given time interval. This study investigates the reliability assessment of Ekpoma 33/11kV Injection substation distribution network on Iruekpen, Irrua, and Express feeders. The reliability indices data were collected from the distribution network daily operational logbook from January to December, 2024; and used to analyzed the reliability indices including power interruptions and outage durations, and customers’ reliability indices using statistical database and Microsoft Excel to plots the Pie charts. Results shown that, Irrua feeder has the least average annual failure rate of 0.1624 event/hr. followed by Express feeder with 0.1647 event/hr. while Iruekpen feeder has the highest recorded failure rate of 0.1716. Iruekpen, Irrua, and Express feeders has Availability values of 61.47%, 63.42%, and 63.71%. These values were considered relatively “fair and consistent” in performance, compared to 99.99% stipulated by IEEE 1366-2022 standard. Express feeder registered the highest SAIFI values of 1.2418, followed by Irrua feeder with values of 0.2868, and Iruekpen feeder with the least values of 0.1324. Meanwhile, MTBF, MDT, SAIDI, CAIDI, ASAI and ASUI were as well analyzed and results presented. Also, interrupted frequency and outage duration were 1503, 1423, 1443; and 3375, 3204 and 3179 in hours for Iruekpen, Irrua, and Express feeders respectively. Major causes of power interruption on these feeders was largely due to long circuits length, configurations, ageing equipment, complete system collapse as a result of under frequency operation, scheduled and forced outages.